Beyond the Khyber Pass: The Road to British Disaster in the First Afghan War by John H. Waller. Austin: University of Texas Press, 1990, 329 + xxxiii pp. (American Journal of Islam and Society, 1995)
John Waller, an American foreign service officer and retired inspectorgeneral of the CIA, is now an independent writer based in McLean,Virginia. He is also the author of Gordon of Khartoum and has travelledextensively in the Middle East and Asia. The book is beautifully illustratedwith photographs of men, women, and events of the time, whichsucceed in invoking visually the time period with which he is dealing: theFirst Afghan-British War.This thirty-chapter book is the story of the British failure inAfghanistan in the 1840s, as Britain competed with Czarist Russia forstrategic advantage in Central Asia. Beyond the Khyber Pass is a sweepingsaga, chronicling the brutal wars and international intrigues of thenineteenth century in India, Afghanistan, Central Asia, and Russia-the"Great Game" that culminated in the siege of Kabul and the massacre ofsixteen thousand British soldiers, their families, and camp followers in1842, the year of the First Afghan-British War. Waller tells the tale ofintrigue, treachery, and wild adventure with relish evident in the juicyanecdotes and asides ...